FROM IMITATION TO EXPRESSION: THE USE OF DIRTY WORDS AMONG ELEMENTARY SCHOOL STUDENTS - Nabillah Putri, Shania; Amelia Safitri, Aliza; Hadiyansyah, Dhuha (Universitas PGRI Palembang, 2025)
This study examines the use of harsh language by elementary school children at a public school in West Jakarta. A qualitative research approach, combining observation and interviews, was used to gather data from 20 participants. The aim was to gain a comprehensive understanding of the usage of offensive language in their environment. The findings reveal five categories of harsh language: Dyspeptic Swearing, Abusive Swearing, Idiomatic Swearing, Emphatic Swearing, and Cathartic Swearing. Additionally, several types of offensive language were identified, including Animal, Sex Organ, Sexual Activity, Scatological, Patronymic, Racial/Ethnic Insults, Ableism, and Body Shaming. The study also highlights that the usage of these offensive terms is influenced by neurological, psychological, and sociocultural factors. The results of this research provide valuable insights into the wide variety of harsh words used by elementary school children and emphasize the need for fostering the use of more positive language among students.